APPLICATION FOR MOBILE AGENT TO ACCESS MYSQL - Sugiantoro, Bambang; Wardoyo, Retantyo; Hartati, Sri; Istiyanto, Jazi Eko (IJID (International Journal on Informatics for Development), 2012)
Availability of information is increasing rapidly, the method for encoding and storage of information also increased. The number of sources of information brings several problems, among them about how to combine the distributed data storage and different. Information on an organization or company is usually stored in separate locations and different formats. When there is an increase in storage capacity and the amount of information search costs, the company faced with an abundance amount of data. System development methodology used is Rapid Application Development (RAD) with a development framework Guidlines for Rapid Application Engineering (GRAPPLE). The software used in building this application is Borland Jbuilder 9. Rational Rose 2000 is used for the analysis and design using Unified Modeling Language (UML). Mysql server is a type of database to be accessed on each operating system. Operating system used in this study is Windows XP and Linux Fedora Core. This application was developed with aglets, which is one of software for building mobile agent applications.